Influence of Job Resources on Organizational Commitment Mediated by Work Engagement - Stevinia Stevinia; Zamralita; Rita Markus Idulfilastri (Dinasti International Journal of Education Management And Social Science, 2023)
Indonesia needs to be wary of the recession era that threatens in 2023. The recession-era can impact an economic slowdown which makes the real sector hold back its production capacity so that recruitment freezes up to layoffs (PHK) can occur. With the occurrence of this phenomenon, the trust of employees who are still working at the company to continue working at the company and make their best contribution becomes very important for the company. This is known as organizational commitment. Factors that affect organizational commitment are work engagement and being influenced by job resources. Therefore, this research aims to determine the effect of job resources on organizational commitment mediated by work engagement. A non-experimental quantitative research approach that applied. The data obtained in this study were analyzed by statistical analysis using SPSS version 23.0 for Windows and Process v3.5 by Andrew F Hayes. This research was conducted on 80 employees at a manufacturing company in West Java. The study results show that work engagement is the perfect mediator between job resources and organizational commitment.